Influence Of Thermal Experience On Thermal Comfort In Naturally Conditioned University Classrooms - J. Y. Shen; S. Kojima; X. Y. Ying; X. J. Hu (International Association of Lowland Technology, 2019)
This study aimed to investigate the relevance of thermal experience on students’ thermal perceptions in the naturally conditioned university classrooms, and identified the suitable values of indoor thermal parameters for students’ thermal comfort in Southeast China. Field measurements on environmental parameters and questionnaire surveys of students’ thermal perceptions were conducted in the whole duration of twelve lectures in summer and winter. Thermal perceptions of TSV, TAV and TPV were recorded 3 times (15min, 45min, 95min) within each survey. It was found that, the indoor thermal conditions for students were more comfortable and acceptable in summer than in winter. Positive correlation of thermal sensation and indoor operative temperature occurred in summer, while negative correlation occurred within the indoor operative temperature range of 9.8 15.3℃ in winter, and only when the initial temperature was upon 15.7℃, could the normal response of students’ thermal sensation on the ambient environment return back. Thermal memory will make impact on the thermal perception as the on-site temperatures lose their control of current thermal response gradually, especially under the extremely cold thermal conditions. Meanwhile, TSV, TAV and TPV were unsynchronized in both summer and winter, especially in winter.